Ditadura residual - Tifaldi, Thiago (2017)
The general objective of this dissertation is the residual dictatorship. Highlight so that you can understand what's left of the civil-military dictatorship, from 1964 to 1985, in the contemporary democratic and, above all, why no progress, or rather, why won't you move, keeping the transition between authoritarianism and democracy, from 1986 to 1988. It is considered to be dictatorial residue which makes the current democratic regime, formally established in 1988, stay stagnant, or rest in a kind of intermediate regime, safety, fostered by the diffuse feelings of fear and insecurity, which recriaria a society eager for militarism. To highlight the residual dictatorship, will be addressed in this essay aspects such How to: maintain repressive apparatus of the civil-military regime of 1964 in democratic rule after 1988, in particular the auxiliary armed forces and army reserve; resistance on if reestruturto them in the context of the current democratic regime; the absence of content or subjects of Military Law in legal education; and, as the proposed ' constitutional ' military intervention, the latest public demonstrations , ria can be interpreted in the context of the dictatorship. Aspects that will be discussed from a theoretical explanatory basis, adding to the primary production data methodology to illustrate the argument